Approach to Quality of Work-Life and Affective Commitment in Sustainable HRM Practices for the improvement of Organizational Citizenship Behavior - Iwan Ardiansyah; Taufiq Rahmat (Politeknik APP Jakarta, 2023)
This study aims to to measure and explain the practice of implementing Sustainable HRM to improve Organizational Citizenship Behavior by using the variables of Quality of Work-Life (QWL) and Affective Commitment, especially in the automotive retail industry. Data analysis uses a path to show a specific relationship between exogenous variables, which are variables (X), endogenous variables which are effect variables (Y), and implicit variables (Ïµ). This data was collected through an array of questions to be answered by replies from as many as 59 motorcycle automotive retail company employees. The QWL and affective commitment have a favourable and considerable impact on OCB in employees. External influences still need to be followed up by further research, which can complement the determination of OCB in addition to QWL and Affective Commitment. Subsequent research focuses on environmental performance management, the design of training and development, and environmental organizational culture.